Petrophysical properties of the 9-km-deep crustal section at KTB - Berckhemer, Hans; Rauen, A.; Winter, H.; Kern, H.; Kontny, Agnes; Lienert, M.; Nover, G.; Pohl, J.; Popp, T.; Schult, A.; Zinke, J.; Soffel, H. C. (Journal of geophysical research. Solid earth, 1997)
Petrophysical properties of drill core and drill cuttings samples from both bore holes of the German Continental Deep Drilling Program (KTB) measured at atmospheric pressure and room temperature in the field laboratory are presented, along with data of core samples measured at simulated in situ conditions by other laboratories. Most of the petrophysical properties show a bimodal frequency distribution corresponding to the two main lithologies (gneiss and metabasite), except electrical resitivity and Th/U ratio which are lithology independent (monomodal distribution). Low resistivities are mainly associated with fractures zones enriched in fluids and graphite. The most abundant ferrimagnetic mineral is monoclinic pyrrhotite. Below 8600 m, hexagonal pyrrhotite with a Curie temperature of 260°C is the stable phase. Thus the Curie isotherm of the predominant pyrrhotite was reached (bottom hole temperature about 265°C). The highest values of magnetic susceptibility are linked with magnetite. Microcracks grow due to pressure and temperature release during core uplift. This process continues after recovery and is documented by the anelastic strain relaxation and acoustic emissions. The crystalline rocks exhibit marked reversible hydration swelling. Anisotropy of electrical resistivity, permeability, P and S wave velocity is reduced significantly by applying confining pressure, due to closing of microcracks. Fluids within the microcracks also reduce the P wave velocity anisotropy and P wave attenuation. Anisotropy and shear wave splitting observed in the field seismic experiments is caused by the foliation of rocks, as confirmed by laboratory measurements under simulated in situ conditions. The petrophysical studies provide evidence that microfracturing has an important influence on many physical rock properties in situ.